1992
DOI: 10.1055/s-2007-994677
|View full text |Cite
|
Sign up to set email alerts
|

Fused Eyelids in the Extremely Premature Infant: Multivariate Analysis of Survival and Outcome

Abstract: The presence of fused eyelids at birth in the extremely low birthweight infant (less than 1000 gm) is often regarded by physicians as an indication of nonviability. This is especially true for the pediatrician who does not have routine exposure to extremely premature infants and may use the presence of fused eyelids to influence the level of resuscitation afforded the infant in the first crucial minutes following birth. Unfortunately, there are scant data in the literature to guide general pediatricians with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Gender differences in neonatal outcome are well known but the underlying mechanisms to explain them remain unclear [36,37]. In the current study, we found a significant influence of gender on the levels of BA-TGF-ß.…”
Section: Discussionsupporting
confidence: 51%
“…Gender differences in neonatal outcome are well known but the underlying mechanisms to explain them remain unclear [36,37]. In the current study, we found a significant influence of gender on the levels of BA-TGF-ß.…”
Section: Discussionsupporting
confidence: 51%
“…Historically, signs from physical examination, such as fusion of the eyelids, were used to determine viability at extremely preterm gestations, although their utility has not been borne out. 34,35 The use of the combined 5 factors in the model was again found to outperform gestational age alone as a tool for predicting survival, 4 and the predictive benefits of a modelbased vs gestational age-based approach were demonstrated in the decision curve analysis. In the future, other methods, such as the use of biochemical markers of infant maturity, may enhance our ability to estimate infant outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The C statistic of the updated model was not substantially different from that observed when deriving the original model and in independent validations of that model and demonstrated the continued difficulty of estimating outcomes for extremely preterm infants at the time of birth. Historically, signs from physical examination, such as fusion of the eyelids, were used to determine viability at extremely preterm gestations, although their utility has not been borne out . The use of the combined 5 factors in the model was again found to outperform gestational age alone as a tool for predicting survival, and the predictive benefits of a model-based vs gestational age–based approach were demonstrated in the decision curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a benefit for caesarean section but did not clarify the issue with respect to sex or other confounders contributing to the incidence of abdominal delivery. The effect of sex on survival has been reported for even the tiniest infants independent of such physical signs of immaturity as fused eyelids 4. In a multivariate logistic regression analysis of infants at the threshold of viability, girls, small for gestational age infants, and infants whose mothers had received antenatal steroids had a reduced risk of death.…”
mentioning
confidence: 99%